Voting at National versus European Elections: An Individual Level Test of the Second Order Paradigm for the 2014 European Parliament Elections - Boomgaarden, Hajo G. (2016)
The second-order paradigm is the dominant framework for research on electoral behavior in European Parliament (EP) elections. In this study, we assess to what degree voting patterns in the 2014 EP election were characterized by second-orderness. While most studies of second-order voting behavior rely on macro-level accounts or suffer from potentially conflated vote measures, this study relies on panel data from the 2013 national and the 2014 EP election in Austria. We study change patterns in electoral behavior and, more importantly, assess the motives behind differences in vote choices between first- and second-order elections. Overall, the findings point towards a persisting relevance of the second-order framework for explaining voting in the 2014 EP election.